Effects of the COVID-19 pandemic on academic preparation and performance: a complex picture of equity - Burkholder, Eric W.; Salehi, Shima (Frontiers in Education, 2023)
Many experts have predicted a drop in students' academic performance due to an extended period of remote instruction and other harmful effects of the pandemic. As university instructors and education researchers, we sought to investigate the effects of the pandemic on students' preparation for college-level coursework and their performance in early college. Data were collected from STEM students at a public research university in the southeastern United States. We found that demographic gaps in high school preparation (as measured by ACT scores) between men and women, underrepresented minority and majority students, and first generation and continuing generation students all increased from the Fall of 2019 to the Fall of 2021. This gap in preparation was not accompanied by a corresponding shift in the demographics of the student population and there was no corresponding increase in the demographic gaps in students' first term grades. The data seem to suggest that those historically marginalized in STEM suffered more from the changes to secondary instruction during the pandemic, but that college instructors were able to mitigate some of these effects on first-semester grades. However, these effects were only mitigated to the extent that they preserved the status quo of pre-pandemic inequities in undergraduate STEM education.